Non-alcoholic fatty liver disease combined with rheumatoid arthritis exacerbates liver fibrosis by stimulating co-localization of PTRF and TLR4 in rats - Zhang, Shengpeng; Zhu, Peng; Yuan, Jianan; Cheng, Kunming; Xu, Qixiang; Chen, Wei; Pan, Zui; Zheng, Yongqiu (Frontiers in Pharmacology, 2023)
Rheumatoid arthritis (RA) has high prevalence in patients with Non-alcoholic fatty liver disease (NAFLD), however, the underlying mechanism is not well known. To address that, this study established a combined model with both NAFLD and RA by administering a high-fat diet (HFD) and intradermal injection of Freund’s complete adjuvant (FCA) with bovine type II collagen. Collagen-induced RA (CIA) was confirmed by hind paw swelling and histological examination. The histomorphological characteristics of NAFLD were evaluated by Masson’s trichrome and hematoxylin–eosin staining. The development of NAFLD was further evaluated by serum concentrates of triglyceride (TG), total cholesterol (T-CHO), alanine aminotransferase (ALT) and aspartate aminotransferase (AST). In this compound rat model, HFD exacerbated secondary inflammation in CIA rats. On the other hand, FCA/bovine type II collagen injection increased serum levels of ALT, AST, TG, and T-CHO and exacerbated hepatic fibrosis in both normal and NAFLD rats. Interestingly, NAFLD+CIA significantly promoted the expression of PTRF, a caveolae structure protein involoving in hepatic lipid metabolism, and affecting downstream signaling of Toll-like receptor 4 (TLR4) and PI3K/Akt activation. High resolution confocal microscopy revealed an increased PTRF and TLR4 co-localizationin hepatic small vessels of NAFLD+CIA rats. AAV9-mediated PTRF knockdown inhibited TLR4 signaling and alleviated hepatic fibrosis in NAFLD+CIA rats. Together, these findings indicate that NAFLD combined with CIA causes synovial injury and enhances non-alcoholic fatty liver fibrosis in rats. PTRF could attenuate the symptoms of NAFLD+CIA likely by affecting TLR4/PTRF co-expression and downstream signaling.